Effect of glyphosate on the growth, morphology, ultrastructure and metabolism of Scenedesmus vacuolatus - Iummato, Maria Mercedes (2019)
The effects of a commercial glyphosate formulation on the oxidative stress parameters and morphology (including the ultrastructure) of the phytoplanktonic green microalga Scenedesmus vacuolatus were evaluated. After 96 h of exposure to increasing herbicide concentrations (0, 4, 6, 8 mg L −1 active ingredient) with the addition of alkyl aryl polyglycol ether surfactant, the growth of the cultures decreased (96 h-IC50- 4.90 mg L −1 ) and metabolic and morphology alterations were observed. Significant increases in cellular volume (103–353%) and dry weight (105%) and a significant decrease in pigment content (41–48%) were detected. Oxidative stress parameters were significantly affected, showing an increase in the reactive oxygen species (ROS) and reduced glutathione (GSH) contents, oxidative damage to lipids and proteins and a decrease in the activities of the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) and the detoxifying enzyme glutathione-S-transferase (GST). Cells exposed to glyphosate formulation were larger and showed an increase in vacuole size, bleaching, cell wall thickening and alteration of the stacking pattern of thylakoids. The results of this study showed the participation of oxidative stress in the mechanism of toxic action of the commercial glyphosate formulation on S. vacuolatus and the relation between the biochemical, morphological and ultrastructure alterations.